Sporobolomyces and Sporidiobolus – non-conventional yeasts for use in industries - Kot, Anna M.; Kieliszek, Marek; Piwowarek, Kamil; Błażejak, Stanisław; Mussagy, Cassamo Ussemane [UNESP] (Elsevier, 2021)
The search for new, biotechnologically useful yeast strains has been carried out in many research centers in the world. Sporobolomyces and Sporidiobolus are examples of such useful yeasts, that can be used as a source of many valuable metabolites in industries. This article describes the modern taxonomy of these yeasts, which resulted from many years of research, including both classical microbiology and genetic analyses. Subsequently, the paper presents a review of scientific studies on the biosynthesis of various extracellular and intracellular metabolites produced by Sporobolomyces and Sporidiobolus yeasts, which are of great importance in the contemporary food, feed, and pharmaceutical industries. Such metabolites include exopolysaccharides, lipids, carotenoids, enzymes, and γ-decalactone. Aiming at developing a sustainable circular bioeconomy, this study considers two directions of use of these yeasts, i.e., as a feed additive and as an antagonist in the biocontrol of plant materials. This article is one of the first to organize the knowledge collected from published studies and present the contemporary scientific achievements and prospects for the biotechnological use of Sporobolomyces and Sporidiobolus yeasts.
Keywords: Biocontrol; Carotenoids; Exopolysaccharides; Lipids; Microbial enzymes; Red yeast; γ-decalactone